Temperature Dependence on Microstructure, Crystallization Orientation, and Piezoelectric Properties of ZnO Films - Ke Deng; Zhonghao Liu; Hulin Liu; Yanxiang Chen; Shang Li; Shuren Guo; Boyu Xiu; Xuanpu Dong; Huatang Cao (Sensors)
This study has investigated the effects of different annealing temperatures on the microstructure, chemical composition, phase structure, and piezoelectric properties of ZnO films. The analysis focuses on how annealing temperature influences the oxygen content and the preferred c-axis (002) orientation of the films. It was found that annealing significantly increases the grain size and optimizes the columnar crystal structure, though excessive high-temperature annealing leads to structural degradation. This behavior is likely related to changes in oxygen content at different annealing temperatures. High resolution transmission electron microscopy (HR-TEM) reveals that the films exhibit high-resolution lattice stripes, confirming their high crystallinity. Although the films exhibit growth in multiple orientations, the c-axis (002) orientation remains the predominant crystallographic growth. Further piezoelectric property analysis demonstrates that the ZnO films annealed at 400 °C exhibit enhanced piezoelectric performance and stable linear piezoelectric behavior. These findings offer valuable support for optimizing the piezoelectric properties of ZnO films and their applications in piezoelectric sensors.